EDUKASI DAN PENDAMPINGAN GIZI PADA REMAJA DI DESA INDRODELIK KECAMATAN BUNGAH - Yasirotul Hikmah; Rahma Fidania Dwik Nuraini; Nur Habibatus Sholihah; Nur Qomaria; Dwi Novri Supriatiningrum (Ghidza Media Jurnal, 2022)
Nutritional problems in Indonesia are still often encountered, such as poor nutrition, poor breakfast habits, and bad drinking habits that can cause anemia. This activity aims to improve and increase adolescent knowledge and maintain normal nutritional status in adolescents in Indrodelik Village, Bungah District, Gresik Regency. This activity uses a combination research method (mixed method research) with primary data obtained directly from respondents through the implementation of baselines (interviews and filling out questionnaires) in Indro Hamlet, Indrodelik Village. Sampling of activities using purposive sampling method which is carried out when taking baseline data and samples taken are included in the inclusion criteria, namely aged 13 to 19 years. The results of this activity are that there is an increase in the level of knowledge before and after counseling and an increase in adolescents' understanding regarding the intake consumed must be nutritionally balanced, although the results of the recall analysis are still not stable from day to day. But it has shown an increase and change in the intake of adolescents from before counseling to after counseling.